Nutrition related knowledge and practices of hypertensive adults attending hypertensive clinics at day hospitals in the Cape Metropole - H. Becker; M. Bester; N. Reyneke; D. Labadarios; K.D. Monyeki; N.P. Steyn (AOSIS, 2004)
The aim of this study was to determine nutrition knowledge and dietary practices of hypertensive adults attending hypertensive clinics at Day Hospitals in the Cape Metropole. Ten Day Hospitals were randomly selected from a total of 31 Day Hospitals and the first participants attending the hypertension clinics per day were recruited. A total of 85 participants were evaluated. The weight, height, waist and hip circumference of each participant was measured, as well as their blood pressure. Knowledge of dietary intake was obtained by completing a questionnaire, during an interview with the patient. Knowledge regarding salt usage indicated that a large percentage (34.1 %) of participants believed that flavour enhancers like Aromat or Fondor could safely be used instead of table salt. Furthermore, 23.5% reported that tinned and smoked meat or fish have a low sodium (salt) content. Fruit and vegetables were perceived as having a positive effect on hypertension by 74.1 % of participants. However, only 15% of the group knew that the recommendation for their usage was five or more servings per day. Only 12.9% of participants in this study had a normal weight (body mass index (BMI) < 25), 25.9% were overweight (BMI 25 - 29.9) and 61.2% were obese (BMI ≥ 30); 84.7% recognized the association between obesity and hypertension. A large waist circumference (> 88cm in women; 102cm in men) was found in 61.2% of participants, however, only 18.2% of black men had such a measurement. Uncontrolled blood pressure readings (> 140/90mm Hg) were found in 61.2% of these patients at the hypertension clinics.